2018
DOI: 10.1002/celc.201801302
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Active Site Identification of Fe−N−C Single‐Atom Catalysts for the Oxygen Reduction Reaction

Abstract: Fe−N−C catalysts for the oxygen reduction reaction (ORR) in proton exchange membrane fuel cells (PEMFCs) are still inferior to the Pt catalysts. The major downsides of Fe−N−C are the low density and ambiguous structural identification of active sites. Fe−N−C single‐atom catalysts (SACs) have shown great potential for maximizing the active site density and can serve as ideal platforms for investigating the nature of active sites. This review starts with a summary of the latest progress in the synthetic strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 115 publications
(69 reference statements)
0
37
0
Order By: Relevance
“…In recent years, with advancements in both atomic-resolution characterization techniques and synthesis techniques, singleatom catalysts (SACs) have become one of the frontiers of PGM-free catalysts [72][73][74][75] . This class of catalysts may have relatively pure catalytic sites that are good for the fundamental research of PGM-free catalysts.…”
Section: Activity Progressed Referring To Doe Volumetric Activity Targetmentioning
confidence: 99%
“…In recent years, with advancements in both atomic-resolution characterization techniques and synthesis techniques, singleatom catalysts (SACs) have become one of the frontiers of PGM-free catalysts [72][73][74][75] . This class of catalysts may have relatively pure catalytic sites that are good for the fundamental research of PGM-free catalysts.…”
Section: Activity Progressed Referring To Doe Volumetric Activity Targetmentioning
confidence: 99%
“…Although the challenge of scalability is not always taken in account, some recent approaches to limit the ion mobility show very promising results; however, since all pyrolytic approaches are based on kinetic stabilization only, the active site density is usually pretty low, with Fe contents typically not exceeding 3 wt%. [12][13][14] In more than 30 years of research, no successful preparation of ORR-active Fe-N-Cs was reported based on the coordination of iron to metal-free nitrogen-doped carbons (NDCs). Obviously, the likelihood of randomly occurring N 4 coordination sites is very low, so that Fe ions will, normally, only be loosely bound to the NDC surface (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%
“…The development of sustainable energy technology of fuel cells and metal‐air batteries, relies on the high‐performance and cost‐effective oxygen reduction reaction (ORR) catalysts [1–3] . The platinum‐based nanomaterials possess high activity in catalyzing the ORR in acidic environment [1,4–5] . However, limited by high cost and scarce resources, large‐scale application of Pt is unrealistic.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen‐coordinated transition metal sites (M−N x , M=Fe, Co, Ni, Mn, etc.) on carbon support have been proved to be a promising type of low‐cost ORR catalysts [1–2,8–9] . However, their intrinsic activity is still inferior to the Pt counterparts in acid electrolytes, and more types of active sites need be explored.…”
Section: Introductionmentioning
confidence: 99%